Amlexanox and Forskolin Prevents Isoproterenol-Induced Cardiomyopathy by Subduing Cardiomyocyte Hypertrophy and Maladaptive Inflammatory Responses - Adzika, Gabriel Komla; Hou, Hongjian; Adekunle, Adebayo Oluwafemi; Rizvi, Ruqayya; Adzraku, Seyram Yao; Li, Kexue; Deng, Qi-Ming; Mprah, Richard; Ndzie Noah, Marie Louise; Adu-Amankwaah, Joseph; Machuki, Jeremiah Ong’achwa; Shang, Wenkang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Chronic catecholamine stress (CCS) induces the occurrence of cardiomyopathy – pathological cardiac hypertrophy (PCH), which is characterized by left ventricular systolic dysfunction (LVSD). Mounting evidence implicates myocardial inflammation in the exacerbation of pathological cardiac remodeling. However, there is currently no well-defined treatment intervention or regimes targeted at both the attenuation of maladaptive myocardial hypertrophy and inflammation during CCS to prevent PCH. G protein-coupled receptor kinase 5 (GRK5) and adenylyl cyclases (ACs)-cAMP mediates both cardiac and inflammatory responses. Also, GRK5 and ACs are implicated in stress-induced LVSD. Herein, we aimed at preventing PCH during CCS via modulating adaptive cardiac and inflammatory responses by inhibiting GRK5 and/or stimulating ACs. Methods: Isoproterenol-induced cardiomyopathy (PCH) was modeled (0.5mg/100g/day isoproterenol injections for 40days). Alterations in cardiac and inflammatory responses were assessed from the myocardia. Similarities in the immunogenicity of cardiac troponin I (cTnI) and lipopolysaccharide under CCS were assessed, and Amlexanox (35μM/ml) and/or Forskolin (10μM/ml) were then employed in vitro to modulate adaptive inflammatory responses by inhibiting GRK5 or activating ACs-cAMP, respectively. Subsequently, Amlexanox (2.5mg/100g/day) and, or Forskolin (0.5mg/100g/day) were then translated into in vivo during CCS to modulate adaptive cardiac and inflammatory responses. The effects of Amlexanox and Forskolin on regulating myocardial systolic functions and inflammatory responses during CCS were ascertained afterward. Results: PCH mice had excessive myocardial hypertrophy, fibrosis, and aggravated LVSDs which was accompanied by massive CD68+ inflammatory cell infiltrations. In vitro, Forskolin-AC/cAMP was effective than Amlexanox-GRK5 at downregulating proinflammatory responses during stress; nonetheless, Amlexanox and Forskolin combination demonstrated the most efficacy in modulating adaptive inflammatory responses. Individually, translated Amlexanox and Forskolin treatment interventions were ineffective at subduing the pathological remodeling and sustaining cardiac function during CCS. However, their combination was very potent at preventing LVSD during CCS by attenuating maladaptive myocardial hypertrophy, fibrosis, and inflammatory responses. Conclusions: The treatment intervention attained its potency mainly via Forskolin-ACs/cAMP-mediated modulation of cardiac and inflammatory responses, coupled with Amlexanox inhibition of GRK5 mediated maladaptive cascades. Taken together, our findings highlight the Amlexanox and Forskolin combination as a potential therapeutic intervention for preventing the occurrence of pathological cardiac hypertrophy during chronic stress.